KESULITAN BELAJAR MATEMATIKA DITINJAU DARI SELF-EFFICACY SYSTEMATIC LITERATURE REVIEW (SLR) - Meicindy Jeny Klorina; Dadang Juandi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
This study aims to describe the results of research on students' learning difficulties in mathematics in terms of self-efficacy. The method used in this study is the Systematic Literature Review (SLR), which consists of 15 samples of the results of research on learning difficulties in mathematics in terms of self-efficacy. The research sample consisted of those indexed by SCOPUS, SINTA to indexed by REPOSITORY in the period 2018-2022 and located in Indonesia. Search sample data obtained from Google Schoolar, Semantic Schoolar Eric Journal, Researchgate, and Repository. Data was collected by documenting all articles related to learning difficulties in mathematics in terms of self-efficacy based on the year of research, type of research, education level, research demographics, and journal index. All data obtained are presented in a quantitative descriptive manner. With the SLR method, it was found that the most research published in 2018, this research was also dominated by research indexed by SINTA 2. The majority of this research was conducted at the junior high school level and this research was dominated on the island of Java. Research on students' learning difficulties in mathematics in terms of self-efficacy tends to be small, researchers mostly examine students' learning difficulties in mathematics, even though knowing the students' self-confidence makes it easier for teachers to avoid learning difficulties that will be experienced by students.